FEATURES OF THE PROCESS OF DEVELOPING CREATIVE ABILITIES IN NATIVE LANGUAGE LESSONS (International journal of artificial intelligence, 2024)
This article examines important features of native language lessons, such as developing not only students' speech skills, but also creative thinking, logical analysis, expressing their thoughts through language, creating new ideas, using modern pedagogical technologies, and forming individual and team work skills.